IMPACT OF TRADITIONAL HANDICRAFT ON SURFACE AND GROUNDWATER QUALITY: A CASE STUDY IN SON DONG VILLAGE, VIETNAM - Xuan Dung, Bui; Thuy Quynh, Kieu; Bao Ngoc, Trieu; Thi Ngoc Anh, Do (Journal of Forestry Science and Technology, 2022)
This study aims to analyze spatial and temporal changes of surface and groundwater quality from March to December 2019, in Son Dong commune, Hoai Duc district, Hanoi. A number of physicochemical parameters were sampled for analysis to give quantitative assessments, and spatial distribution as well as temporal variation were performed. Surface water samples were collected along the commune canal route at different depths (20 and 30 cm) and groundwater samples were taken from drill-wells. From March to December 2019, 10 groundwater samples and 5 surface water samples were collected. 7 surface water parameters including: Fe, NH4+, Mn, NO2-, Cu, TSS and pH, 8 groundwater parameters including: Fe, NH4+, Mn, NO2-, Cu, pH, TDS, and hardness were analyzed. Based on analyzed water quality findings, both surface and groundwater in Son Dong are heavily polluted compared to the standard of Ministry of Natural Resources and Environment. The indicators of pH, TSS, TDS and NO2-, were almost unchanged and lower than the permitted value. Water quality in the study area is contaminated with heavy metals. The analysis results of NH4+, Cu, Fe parameters are higher than the permitted standards QCVN 08: 2015/TNMT for surface water and 09: 2015/TNMT for groundwater. The groundwater quality index (GWQI) was calculated based on the analyzed criteria is higher than 200, which means it is not suitable for drinking. The most polluted areas are in the south and northwest of Son Dong commune. Therefore, in the face of poor water quality, it is necessary to have some suitable solutions to improve water quality in the study area.